Review paperPhysics-aspects of dose accuracy in high dose rate (HDR) brachytherapy: source dosimetry, treatment planning, equipment performance and in vivo verification techniques - Palmer, Antony; Bradley, David; Nisbet, Andrew (Journal of Contemporary Brachytherapy, 2012)
This study provides a review of recent publications on the physics-aspects of dosimetric accuracy in high dose rate (HDR) brachytherapy. The discussion of accuracy is primarily concerned with uncertainties, but methods to improve dose conformation to the prescribed intended dose distribution are also noted. The main aim of the paper is to review current practical techniques and methods employed for HDR brachytherapy dosimetry. This includes work on the determination of dose rate fields around brachytherapy sources, the capability of treatment planning systems, the performance of treatment units and methods to verify dose delivery. This work highlights the determinants of accuracy in HDR dosimetry and treatment delivery and presents a selection of papers, focusing on articles from the last five years, to reflect active areas of research and development. Apart from Monte Carlo modelling of source dosimetry, there is no clear consensus on the optimum techniques to be used to assure dosimetric accuracy through all the processes involved in HDR brachytherapy treatment. With the exception of the ESTRO mailed dosimetry service, there is little dosimetric audit activity reported in the literature, when compared with external beam radiotherapy verification.